Analisis Penerapan Standar Akuntansi Pemerintahan (SAP) Terhadap Transparansi dan Akuntabilitas Laporan Keuangan Pemerintah Daerah Desa Amplas - Neysha Septry Tarigan; Rimbun C.D.Sidabutar; Magdalena J Siringoringo (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Village financial management that is transparent and accountable has become an important issue along with the increasing allocation of village funds. However, the implementation of Government Accounting Standards (SAP) at the village level still faces various challenges, making it necessary to be examined empirically. This study aims to analyze the implementation of SAP and its impact on the transparency and accountability of financial statements in the Government of Amplas Village, Percut Sei Tuan District, Deli Serdang Regency. This research employs a qualitative approach with a case study method. Data were collected through in-depth interviews with informants selected using purposive sampling, including the village head, village secretary, financial officer, general and planning officer, and community representatives. The study was conducted over a period of approximately three to five months. The results indicate that the Amplas Village government has implemented SAP principles in village financial management through systematic transaction recording, periodic preparation of financial reports, and dissemination of financial information to the community through village meetings and information media. The implementation of SAP contributes to improving the transparency and accountability of village financial reports, although it is not yet optimal due to limited human resources and technical understanding of village officials. The implications of this study highlight the importance of enhancing the capacity of village officials through training and the utilization of information technology in financial management to achieve more transparent and accountable governance.